2020
DOI: 10.3390/ijerph17030960
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Incidence in U.S. Counties and Low Levels of Arsenic in Drinking Water

Abstract: Background: Although inorganic arsenic in drinking water at high levels (100s–1000s μg/L [ppb]) increases cancer risk (skin, bladder, lung, and possibly prostate), the evidence at lower levels is limited. Methods: We conducted an ecologic analysis of the dose-response relationship between prostate cancer incidence and low arsenic levels in drinking water in a large study of U.S. counties (N = 710). County arsenic levels were <200 ug/L with median <100 ug/L and dependency greater than 10%. Groundwater wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The population-based study focused on the dose–response relationship between prostate cancer and high As exposure from drinking water and recognized their interconnection in 1980 [ 25 ]. Since then, the latest studies by Ahn et al [ 72 ] and Bulka et al [ 73 ] confirmed a significantly higher incidence of prostate cancer in people consuming drinking water with higher As levels. Contrary to significantly higher As serum levels in prostate cancer patients demonstrated by Lim et al, the results of the present study revealed significantly lower blood As levels ( p < 0.05) in the prostate cancer patients of the Serbian cohort in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The population-based study focused on the dose–response relationship between prostate cancer and high As exposure from drinking water and recognized their interconnection in 1980 [ 25 ]. Since then, the latest studies by Ahn et al [ 72 ] and Bulka et al [ 73 ] confirmed a significantly higher incidence of prostate cancer in people consuming drinking water with higher As levels. Contrary to significantly higher As serum levels in prostate cancer patients demonstrated by Lim et al, the results of the present study revealed significantly lower blood As levels ( p < 0.05) in the prostate cancer patients of the Serbian cohort in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Micro- and nanoplastics would not be the first toxic substance to induce mitohermesis; low-dose arsenite has been show to induce mitohormesis thus increasing lifespan (Schmeisser et al, 2013) and could potentially be linked to reduced risk of cancer (Ahn et al, 2020; Baastrup et al, 2008). However, it is important to understand at which dose PET might provide a beneficial effect via hormesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research and case reports have also shown a link between arsenic exposure and cancer. Arsenic exposure has been linked to skin [ 77 ], lung [ 78 ], liver [ 79 ], kidney [ 80 ], bladder [ 81 ], and prostate cancers [ 82 ].…”
Section: Discussionmentioning
confidence: 99%